Public stealth and boundary objects: Coping with integrated water resource management and the post-political condition in Montana's portion of the Yellowstone River watershed. Issue 83 (July 2017) - Ward, Lucas; Anderson, Matthew B.; Gilbertz, Susan J.; McEvoy, Jamie; Hall, Damon M.
Abstract: This paper uses the case of recent efforts in the Yellowstone River watershed to illuminate how the implementation of Integrated Water Resources (IWRM)-styled activities by a Montana state agency is best understood as an exercise in practical expediency that indirectly, but consequentially, supports hegemonic neo-liberalism. We present an innovative use of Q method, focus groups, and participant observations, as means to examine how scale-based interventions by the state moved IWRM-style reforms forward. The activities under consideration allow us to advance an empirically-based critique of so-called integrated approaches to environmental reform with a specific focus on the rescaling process inherent to adoption of the IWRM model. We argue that efforts to transition to IWRM-style governance are likely to be accompanied by stealthy, scale-based interventions. We use the concepts of "standardized packages" and "boundary objects" to raise questions about the degree to which use of such tactics should be interpreted as evidence of a broader hegemonic project to further imbricate neoliberal governmentality, as the literature on post-politics would suggest, or whether eco-scaling and careful circumscription of participation are simply the most convenient strategies for those charged with difficult and complex tasks.